2003
DOI: 10.1046/j.1432-1033.2003.03411.x
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor‐independent oxygenation reactions catalyzed by soluble methane monooxygenase at the surface of a modified gold electrode

Abstract: Soluble methane monooxygenase (sMMO) is a three-component enzyme that catalyses dioxygen-and NAD(P)Hdependent oxygenation of methane and numerous other substrates. Oxygenation occurs at the binuclear iron active centre in the hydroxylase component (MMOH), to which electrons are passed from NAD(P)H via the reductase component (MMOR), along a pathway that is facilitated and controlled by the third component, protein B (MMOB). We previously demonstrated that electrons could be passed to MMOH from a hexapeptide-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In a further study, Astier et al [9] found that the same enzyme could, under some conditions, adsorb robustly but nondestructively to this peptide interface.…”
mentioning
confidence: 90%
“…In a further study, Astier et al [9] found that the same enzyme could, under some conditions, adsorb robustly but nondestructively to this peptide interface.…”
mentioning
confidence: 90%
“…) that rapidly and irreversibly inhibit the reductase subunit of the enzyme, preventing electron transfer to the hydroxylase subunit (Green et al, 1985;Jahng & Wood, 1996); and (iii) H 2 O 2 , which inactivates the enzyme through an unknown mechanism (Astier et al, 2003). Because propionate lacked structural similarity to any of the known inhibitors and inactivators of sMMO mentioned above, we thought it worthwhile to characterize the effect of propionate on BMO.…”
Section: +mentioning
confidence: 99%
“…In the context of existing literature on sMMO, two possible mechanisms for propionate-dependent inactivation of BMO can be proposed. First, in vitro studies showed that when sMMO hydroxylase is electrically reduced at the surface of an electrode, O 2 is reduced to H 2 O 2 by the hydroxylase and subsequently inactivates it (Astier et al, 2003). We propose a model of BMO inactivation in which propionate stimulates the production of H 2 O 2 by BMO and causes oxidative enzyme damage.…”
mentioning
confidence: 93%
See 2 more Smart Citations